2020
DOI: 10.1177/1352458520908037
|View full text |Cite
|
Sign up to set email alerts
|

Concussion in adolescence and the risk of multiple sclerosis: A retrospective cohort study

Abstract: Background: Physical trauma, specifically concussions sustained during adolescence, has been hypothesized to be a risk factor for multiple sclerosis (MS). Objective: To examine the association between adolescent concussions and future MS diagnosis. Methods: This retrospective study using linked administrative databases from Ontario, Canada, identified 97,965 adolescents (age 11–18 years) who sustained ⩾1 concussion and presented to an emergency department between 1992 and 2011. Cases were matched 1:3 with indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(36 reference statements)
1
3
1
Order By: Relevance
“…(Montgomery et al., 2017 ) A Canadian study of nearly 100,000 pTBI patients had similar findings to Swedes. They found out that TBI in adolescence (age 11−18) increases the risk of multiple sclerosis (HR = 1.29), but unlike our results, they demonstrated that the risk was higher among males (HR = 1.41), whereas our study demonstrated over 1.5 times higher risk for women (Povolo et al., 2021 ). The Canadian study was also similar in study design to ours and they studied retrospectively TBI patient cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…(Montgomery et al., 2017 ) A Canadian study of nearly 100,000 pTBI patients had similar findings to Swedes. They found out that TBI in adolescence (age 11−18) increases the risk of multiple sclerosis (HR = 1.29), but unlike our results, they demonstrated that the risk was higher among males (HR = 1.41), whereas our study demonstrated over 1.5 times higher risk for women (Povolo et al., 2021 ). The Canadian study was also similar in study design to ours and they studied retrospectively TBI patient cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Compared to the few other previously published studies, our find- our results, they demonstrated that the risk was higher among males (HR = 1.41), whereas our study demonstrated over 1.5 times higher risk for women (Povolo et al, 2021). The Canadian study was also similar in study design to ours and they studied retrospectively TBI patient cohort.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Secondly, medical records could be examined to attempt to determine when the triggers occurred that disrupt the equilibrium sufficiently to cause one or more of the undesired FGID manifestations. Such utilization of patient records can be very informative ( 20 ).…”
Section: The Life Spectrum and Timingmentioning
confidence: 99%
“… 5 The interactions with HLA genes suggest that the mechanisms of these environmental factors relate to the adaptive immune system. 6 Recent large register-based studies have reported an increased risk of MS following traumatic brain injury, 7 8 particularly if repeated and requiring longer hospital care. 8 Traumatic brain injury, following a physical impact to the head, may result in long-lasting dysfunction of the blood–brain barrier and neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%